THE LOCATION, HOUSE, OR NEIGHBOURHOOD CHOICE PREFERENCES AMONG MALAYSIAN HOUSING GENERATIONS - Ismail, Hafiszah; Shaari, Shazwan Mohamed (Journal of Surveying, Construction and Property, 2020)
Demographics and population have been evidenced as part of the key elements that affect property development. Changes in demographics specifically may influence the economy including the property market hence influences the generations. Behaviour and values divergences among various age groups (generations) resulted in a variance of housing choices and decisions made. The generations are the population categorised by the age cohort including the Baby Boomers, Generation X (Gen-X), Generation Y (Gen-Y) and Generation Z (Gen-Z). This study aims to offer a comprehensive overview of housing decisions via choices made between location, house, and neighbourhood between Malaysian generations. This study uses mixed methods approaches with the Selangor state as a case study. The Pair-wise and Analytic Hierarchy Process (AHP) methods of data analyses used for consumer behavioural decision-making studies were adopted in this study to determine the preferences of future housing choice between location, house and neighbourhood. The analysis uncovers house, location and neighbourhood as the prime housing choices factors of the Malaysian generations. The findings evidenced likeliness and differences of housing decision by generations on the choices made. Most importantly, the findings are significant in contributing better understanding and grant indications to the local authorities and housing developers on the main attraction factors of housing choice preferred by generations that may be very valuable for the enhancement of future Malaysian housing provisions.